Opioid agonist treatment take-home doses ('carries'): Are current guidelines resulting in low treatment coverage among high-risk populations in Canada and the USA? - Cayley Russell; Shannon Lange; Fiona Kouyoumdjian; Amanda Butler; Farihah Ali (BMC, 2022)
Abstract Opioid agonist treatment (OAT) is the primary intervention for opioid use disorder (OUD) in Canada and the USA. Yet, a number of barriers contribute to sub-optimal treatment uptake and retention, including daily-supervised medication administration. Thus, clients are eventually granted access to take-home OAT doses (i.e., 'carries') to reduce this burden. However, this decision is based on physician discretion and whether patients can demonstrate stability in various life domains, many of which are inextricably linked to the social determinants of health (SDOH). Current Canadian and USA OAT carry guidance documents are not standardized and do not take the SDOH into consideration, resulting in the potential for inequitable access to OAT carries, which may be the case particularly among marginalized populations such as individuals with OUD who have been released from custody. This perspective article posits that current OAT guidelines contribute to inequities in access to OAT carries, and that these inequities likely result in disproportionately low coverage for OUD treatment among some high-risk groups, including individuals on release from incarceration in particular. Relevant impacts of COVID-19 and related policy changes are considered, and suggestions and recommendations to amend current OAT guidance documents are provided.